Enhanced sonocatalytic treatment of ibuprofen by mechanical mixing and reusable magnetic core titanium dioxide - Kang, K.; Jang, M.; Cui, M.; Qiu, P.; Na, S.; Son, Y.; Khim, J. (Elsevier, 2015)
As a reusable sonocatalyst, magnetically separable titanium dioxide (MST) was synthesized by a sol-gel method and was evaluated in the removal of ibuprofen (IBP). MST was carefully characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), N-2 gas isotherms, band-gap energy, magnetization, zeta potential, and particle size distribution. The kinetics of IBP removal by sonolysis or MST-assisted sonocatalysis was systematically evaluated with various operational parameters such as pH, temperature, ultrasound (US) frequency, and mechanical mixing intensity. For the first time, authors found that mechanical mixing had an opposite effect on the oxidation rate constants of IBP removal by sonolysis or sonocatalysis according to US frequency. Specifically, the magnitude orders of oxidation rate constants in sonolysis and sonocatalysis with mixing (350 rpm) were the same (35 > 1000 > 300 > 500 > 700 kHz), but sonolysis without mixing showed the following order: 500> 1000 >35 kHz. In addition, the removal rate constant of IBP by sonocatalysis at the lowest US frequency (35 kHz) increased exponentially as the mechanical mixing speed increased. MSM exhibited a high reusability because it has similar rate constants with an average value of 17 +/- 0.3 x 10(-3) min(-1) five repetitive kinetic tests. (C) 2014 Elsevier B.V. All rights reserved.